Impact of the components of Mediterranean nutrition regimen on long-term prognosis of diabetic patients with coronary artery disease - Soheila Mosharraf (ARYA Atherosclerosis, 2013)
BACKGROUND: The impact of different nutritional regimens on long-term prognosis and outcome in diabetic patients with coronary artery disease (CAD) has been questioned. Therefore, the objective of the present study was to determine the effects of different nutritional components of Mediterranean regimen on long-term cardiovascular events in diabetic patients with CAD in the Iranian population. METHODS: In a prospective cohort study, we recruited 233 consecutive patients with the diagnosis of type 2 diabetes mellitus and with at least 6 months of documented CAD. Nutritional assessment was obtained by a validated semi-quantitative food frequency questionnaire (FFQ) and the diet score was calculated on the basis of the Mediterranean diet quality index (Med-DQI). For Assessing long-term CAD prognosis, the patients were followed by telephone for one year. The study endpoint was long-term major adverse cardiac and cerebrovascular event (MACCE). RESULTS: Death was observed in 19 patients (8.2%) during the one-year follow-up. Two patients (0.9%) suffered non-fatal myocardial infarction and 14 (6.0%) needed revascularization within 1 year after discharge from hospital. Overall MACCE within one year in the study population was 12.4%. There were significant differences between number of deaths and dietary scores of saturated fatty acid, cholesterol, meats, fish, and fruit and vegetables (P < 0.05). Moreover, significant differences were found between MACCE rate and dietary scores of saturated fatty acid, cholesterol, and fruit and vegetables (P < 0.05). Using multivariate logistic regression models, Mediterranean dietary regimen could effectively predict long-term death as well as MACCE adjusted for gender and age variables. CONCLUSION: Mediterranean dietary regimens, including low level of cholesterol and saturated fatty acid, can effectively improve long-term outcome including death and MACCE in diabetic patients with CAD.   Keywords: Diabetes Mellitus, Coronary Artery Disease, Nutrition